Implicit Modelling of the Las Bambas Deposits, Peru. Issue 1 (1st December 2018) - Reed, Anthony; Cannell, James
Abstract : 3D implicit geological models are employed to better visualise, understand, and utilise all available data. They foster environments of robust dynamic analysis and interpretations, theoretical extrapolation and quantification of rock properties and mineral abundance. Through their use they encourage rigorous scientific discussion by allowing hypotheses to be explored virtually; maximising discovery and expansion. The development of an implicit model for MMG's flagship project, Las Bambas in southern Peru, has advanced the understanding of the mineralising systems along with resource expansion and exploration opportunities. This model not only effectively demonstrates the major features of the system, but also provides a versatile experimental environment in which geological theories and generation of predictive geometries can, and are, frequently queried. Las Bambas is a world class cluster of Cu deposits in the high Andes containing 12.8 Mt of contained copper. Eocene stocks, sills and dike swarms intruded Lower Cretaceous limestones of the Ferrobamba Formation, resulting in the generation of garnet-pyroxene-epidote-magnetite skarns, which were mineralised via magmatic-hydrothermal fluids flowing through permeable zones in the skarns and filling voids with bornite, chalcopyrite, chalcocite, and molybdenite mineralisation. In this presentation, the value of implicit modelling is demonstrated by visualising the complex porphyry and skarn systems at Las Bambas, highlighting how it serves as an effective medium for illustrating deposit geometries and mineralisation relationships.